Checklist of the mites of Pakistan - Halliday, Bruce; Kamran, Muhammad; Bashir, Muhammad Hamid (Zootaxa, 2018)
We present the first comprehensive inventory of the mites of Pakistan, based on data from published books and papers. The fauna as presently understood includes 126 families, 316 genera, and 1105 species. The best-documented genera are those that include pests of stored food (for example Acotyledon, 28 species), plant pests (Brevipalpus, 49 species; Tenuipalpus, 35 species), and beneficial predators (Euseius, 44 species; Neoseiulus, 37 species; Phytoseius, 36 species; Typhlodromus, 47 species). Some economically important families such as the Eriophyidae are almost completely unknown. Some of the Cryptostigmata have been studied, but other groups of soil mites are very poorly known. Other large groups such as the feather mites, water mites, Uropodina, and parasitic Astigmata and Prostigmata, have not been studied in a systematic way. An increase in knowledge of these groups would help an assessment of their economic importance, and would make a valuable contribution to the biogeography of the western section of the Oriental Region and the southern section of the Palaearctic Region.